Potential allopolyploid origin of Ericales revealed with gene-tree reconciliation - Nie, Shuai; Tian, Xue-Chan; Kong, Lei; Zhao, Shi-Wei; Chen, Zhao-Yang; Jiao, Si-Qian; El-Kassaby, Yousry A.; Porth, Ilga; Yang, Fu-Sheng; Zhao, Wei; Mao, Jian-Feng (Frontiers in Plant Science, 2022)
Few incidents of ancient allopolyploidization (polyploidization by hybridization or merging diverged genomes) were previously revealed, although there is significant evidence for the accumulation of whole genome duplications (WGD) in plants. Here, we focused on Ericales, one of the largest and most diverse angiosperm orders with significant ornamental and economic value. Through integrating 24 high-quality whole genome data selected from ~ 200 Superasterids genomes/species and an algorithm of topology-based gene-tree reconciliation, we explored the evolutionary history of in Ericales with ancient complex. We unraveled the allopolyploid origin of Ericales and detected extensive lineage-specific gene loss following the polyploidization. Our study provided a new hypothesis regarding the origin of Ericales and revealed an instructive perspective of gene loss as a pervasive source of genetic variation and adaptive phenotypic diversity in Ericales.